CONTROL OF JUVENILE DELINQUENCY THROUGH COUNSELING SERVICES GROUP IN STATE SMP NEGERI 8 PADANGSIDIMPUAN ACADEMIC YEAR 2015-2016 - Malim Soleh Rambe (Ristekdik : Jurnal Bimbingan dan Konseling, 2016)
The study is based on the problem of juvenile delinquency levels are still students in the school environment, and the general problem of this research is "how juvenile delinquency through group counseling services to reduce juvenile delinquency students of SMP Negeri 8 Padangsidimpuan". The purpose of this research is to find out how the students' understanding of juvenile delinquency before and after the given group counseling services in SMP Negeri 8 Padangsidimpuan. The location of this research in SMP Negeri 8 Padangsidmpuan year 2015-2016 Doctrine located at Jln Tengku rijal Nurdin.kilo meter 7 Average time of research conducted over two (2) months. The study population numbering as many as 254 students and the sample is about 20 students. Based on the problems and objectives, this type of research is quantitative research in the form of True Experimental Design. Data collection tool is questionnaire. Analysis of the data in this study is the technique of Wilcoxon signed rank test data (Wilcoxon Signed Rank test) using SPSS version 20.00. The findings in the experimental group and the control group there is a significant drop between the results and posttest posttest control experiment. The average variable deviant behavior of students at 155.0000 (posttest experiment) while the control group amounted to 140.9000 (posttest control). It looks a very significant difference. The results show that the data processing control juvenile delinquency through group counseling services can reduce students' understanding of juvenile delinquency in class VII-5 SMP Negeri 8 Padangsidimpuan. The conclusion of these results show that the control of juvenile delinquency through group counseling services can reduce juvenile delinquency in class VII SMP Negeri 8 padangsidimpun